1989
DOI: 10.1099/0022-1317-70-7-1641
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Infection of the Central Nervous System by the Macaque Immunosuppressive Type D Retrovirus, SRV-1

Abstract: SUMMARYThe aetiological agent of spontaneously occurring simian acquired immune deficiency syndrome (SAIDS) in rhesus monkeys (Macaca mulatta) at the California Primate Research Center is a type D retrovirus designated SAIDS retrovirus serotype 1 (SRV-1). SRV-1 DNA and RNA have previously been detected in the brains of rhesus monkeys with SAIDS in the absence of viral antigen or neuropathological lesions. In this study we further define the relationship between SRV-1 and the central nervous system (CNS) in rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Using anti-SRV/D-1 gp20 monoclonal antibody (F2-1), virus specific signals were observed at the end portion of the ducts in salivary glands similar to that reported in rhesus macaques infected with SRV/D-1 ( Fig. 2A) [16]. When a newly developed nucleic acid hybridization technology (ISH-AT-CSA) [15] was applied to another section of the same salivary gland sample, similar SRV/D-T signals were observed in the duct (Fig.…”
Section: Detection Of Virus In Salivary Glands By Immunohistochemistrsupporting
confidence: 65%
“…Using anti-SRV/D-1 gp20 monoclonal antibody (F2-1), virus specific signals were observed at the end portion of the ducts in salivary glands similar to that reported in rhesus macaques infected with SRV/D-1 ( Fig. 2A) [16]. When a newly developed nucleic acid hybridization technology (ISH-AT-CSA) [15] was applied to another section of the same salivary gland sample, similar SRV/D-T signals were observed in the duct (Fig.…”
Section: Detection Of Virus In Salivary Glands By Immunohistochemistrsupporting
confidence: 65%
“…Type D simian retroviruses (SRVs) were once common in domestically bred rhesus macaques and the most frequent cause of acquired immunodeficiency in this species. 31,4143,86 Affected animals were viremic but variably seropositive, often developing progressive wasting, diarrhea, and opportunistic infections. Clinically, the disease overlaps with the condition caused by natural or experimental infection of rhesus macaques with SIVmac, but it differs in several important respects.…”
Section: Molecular Assay Characteristics and Techniquesmentioning
confidence: 99%
“…Serial titration assays suggested that during natural infection, SRV is detected in only 1 in 750 to 1 in 25,000 circulating lymphocytes [6]. Immunohistochemistry, Southern blot studies, and electron microscopy have revealed the presence of the virus in epithelial cells of the gastrointestinal tract, mouth, salivary glands, and choroid plexus, as well as in lymphoid cells in lymph nodes, spleen, and thymus [40–43]. Interestingly, SRV‐1 nucleic acids, in the absence of detectable antigens or neuropathy, have been detected in the choroid plexus epithelial cells and spinal fluid, suggesting viral latency in the central nervous system [42].…”
Section: Pathology and Pathogenesismentioning
confidence: 99%